PEMBERIAN SUPLEMEN KOLAGEN TERHADAP KADAR GULA DARAH PADA WANITA MENOPAUSE - Dewi Rosalina; Sri Dinengsih; Risza Choirunissa (Program Studi Kebidanan Fakultas Kedokteran Universitas Malahayati, 2021)
ABSTRACT GIVING COLLAGENT SUPPLEMENTS ON BLOOD SUGAR LEVELS IN MENOPAUSE WOMEN Background: Menopause is a natural process experienced by every woman aged around 48-54 years. The factors that affect menopause at the beginning are usually due to indiscriminate food consumption so that menopausal women experience diabetes mellitus which is increasing where it is known that blood sugar levels can increase.Purpose: This study was to determine the effect of collagen supplementation on blood sugar levels in menopausal women suffering from Diabetes Mellitus in the Work Area of the Curug Public Health Center, Tangerang Regency, 2020.Method: This study was a quasi-experimental study with a One Group Pretest-Postest Design without a control group. The sampling technique used was total sampling. The sample in this study consisted of 20 menopausal women who suffered from diabetes mellitus in June-July 2020.Results: the results of this study indicated that blood sugar levels in menopausal women before being given collagen supplements were 277.15 and after being given collagen supplements 260.30. The results of the Paired t-test analysis showed that there was no effect of blood sugar levels in menopausal women suffering from diabetes mellitus, before and after giving collagen supplements with a value of Pvalue = 0.471.Conclusion : the conclusion is that there is no effect of blood sugar levels before and after giving collagen supplements to menopausal women suffering from diabetes mellitus in the Work Area of the Curug Public Health Center, Tangerang Regency, 2020Suggestion: It is hoped that further research can carry out further research on collagen supplementation in menopausal women on blood sugar levels with a longer / longer study time and add other variables that have not been studied. Keywords: Menopause, Blood Sugar, Collagen. ABSTRAKLatar Belakang: Menopause merupakan proses alamiah yang dialami setiap wanita yang berusia sekitar 48-54 tahun, faktor yang mempengaruhi menopause pada awal biasanya dikarenakan konsumsi makanan yang sembarangan sehingga wanita menopause mengalami diabetes mellitus semakin meningkat dimana telah ketahui kadar gula darah dapat meningkat.Tujuan : Penelitian ini untuk mengetahui pengaruh pemberian suplemen kolagen terhadap kadar gula darah pada wanita menopause yang menderita Diabetes Mellitus di Wilayah Kerja Puskesmas Curug Kabupaten Tangerang Tahun 2020.Metode : Penelitian ini quasi-experiment dengan rancangan One Group Pretest-Postest Design tanpa adanya kelompok kontrol.Teknik pengambilan sampel yang digunakan adalah total sampling. Sampel dalam penelitian ini berjumlah 20 wanita menopause yang menderita diabetes mellitus pada bulan juni-juli tahun 2020Hasil penelitian ini menunjukkan bahwa kadar gula darah pada wanita menopause sebelum diberikan suplemen kolagen 277,15 dan sesudah diberikan suplemen kolagen 260,30. Hasil analisis Uji Paired t-test menunjukan bahwa tidak ada pengaruh kadar gula darah pada wanita menopause yang menderita diabetes mellitus,sebelum dan sesudah pemberian suplemen kolagen dengan nilai Pvalue =0,471.Kesimpulan tidak ada pengaruhkadar gula darah sebelum dan setelah pemberian suplemen kolagen pada wanita menopause yang menderita diabetes mellitus di Wilayah Kerja Puskesmas Curug Kabupaten Tangerang Tahun 2020Saran : diharapkan untuk penelitian selanjutnya dapat melakukan penelitian lebih lanjut mengenai suplemen kolagen pada wanita menopause terhadap kadar gula darah dengan waktu penelitian yang lebih panjang/lamadan menambahkan variable-variabel lain yang belum di teliti. Kata Kunci :Menopause, Kadar Gula Darah ,Suplemen Kolagen